The Interpersonal Whole-Brain Model of Care® (IWBMC™), Cognition, and Academic Performance A Case Study of an Autistic Child - Haynes, Holly; Gonzalez, Julian; Saunders, Allegra; O'Dell, Amy (Technium Social Sciences Journal, 2025)
The prevalence of autism spectrum disorder (ASD) diagnoses has increased significantly, with current Center for Disease Control data indicating 1 in 36 children are diagnosed with ASD. Individuals with ASD often face educational challenges stemming from differences in neural and cognitive development. While numerous therapeutic approaches exist, the diverse nature of ASD necessitates individualized interventions. This case study investigates how an integrated model of care affects the academic performance and cognitive functioning of an adolescent diagnosed with ASD. We tracked one participant's progress through the Interpersonal Whole-Brain Model of Care® (IWBMC™) over six years using a longitudinal single-subject design. We collected data through EG assessments, cognitive functioning measures, and standardized academic testing (WRAT4). Results demonstrated improvements across all domains: neurological functioning showed normalization of brain wave patterns, cognitive measures improved across different tasks, and academic performance advanced by 2-5 grade levels in core subjects. While generalizability is limited by the single-subject design, findings suggest that the IWBMC™ model's individualized approach and foundation in empathetic therapeutic alliance may effectively support development across multiple domains for individuals with ASD. This study provides a foundation for larger-scale investigations of integrated intervention approaches.